الطبيعة القانونية للمحررات الالكترونية ومدى حجيتها في الإثبات (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعيش العالم اليوم تطور هائل في مجال الاتصالات والتقنيات الحديثة، وهو ما أدى إلى ظهور مبدأ التعاملات الالكترونية على كافة الأصعدة. ومن أهم مبادئ هذه التعاملات الالكترونية هي وجود ما يسمى بالمحررات الالكترونية التي تحتوي على الكتابة الالكترونية والتوقيع الالكتروني. ومع مرور الوقت برزت الحاجة الماسة لإثبات هذه التصرفات الالكترونية التي تتم بوسائل التكنولوجيا الحديثة من حاسب وانترنت، مما دعا المشرعين ورجال القانون إلى دراسة شاملة ومعمقة لهذه التصرفات القانونية وأوجدوا أدلة الإثبات المناسبة لهذا التطور محاولين معالجة وضبط المسائل القانونية التي أثيرت أمامهم. سنحاول في بحثنا شرح مبدأ من مبادئ الإثبات وهو مبدأ الثبوت بالكتابة بمفهومه التقليدي، وبعدها دراسة تأثير التطور التكنولوجي التقني على هذا المبدأ ومدى حجية المحرر الورقي والمحرر الالكتروني وما يتبعه من آثار.   Today, the world is witnessing a tremendous development in the field of communications and modern technologies, which has led to the emergence of the principle of electronic transactions at all levels. One of the most important principles of these electronic transactions is the urgent need for so-called electronic documents that contain electronic writing and electronic signature. With the time, there was an urgent need to prove these electronic actions by means of modern technology, such as computers and Internet, which required legislators and jurists to conduct a comprehensive and deep study of these legal actions. They create appropriate evidences for this development, trying to control the legal issues raised before them. In our research, we will try to explain one of the principles of proof, namely the principle of proving in writing in its traditional sense, and then to study the effect of technological development on this principle and the parity between the paper document and the electronic document and the subsequent effects.